Failure to Complete Cross-Border M&As: “To” vs. “From” Emerging Markets - Zhou, Chenxi; Xie, Jinhong; Wang, Qi (Journal of International Business Studies, 2016)
While cross-border mergers and acquisitions (M&As) involving emerging markets have been increasing in recent years, a high percentage collapse before completion. This study investigates how the predictors of cross-border M&A completion involving emerging markets depend upon the direction of global expansion, i.e., investment inbound to a developing market or outbound from a developing market. Analysis based on 15 years of data from four emerging economies, Brazil, Russia, India, and China, from 1995 to 2010, reveals fundamental differences in the predictors of inbound vs. outbound M&A completion. Country-level factors reflecting differences in political, trade, and legal environments strongly affect the completion for inbound M&As, but have a much weaker influence on outbound M&As. By contrast, firm-level factors such as past M&A experience have a significantly stronger effect on completion for outbound than for inbound M&As. Most interestingly, two deal-level factors (the percentage of stake sought by the acquirer and whether or not the deal is a cash transaction) increase the likelihood of completion for inbound but decrease it for outbound M&As. These findings have important managerial implications for enhancing the success of global expansions.